What drives people's opinions of electricity infrastructure? Empirical evidence from Ireland - Valentin Bertsch; Marie Hyland; Michael Mahony (The Economic and Social Research Institute (ESRI), 2016)
Across the EU, significant infrastructure investment is needed in both generation from renewable energy sources (RES) and the electricity transmission system to meet the European targets on emission reduction and RES expansion. Experiences show, however, that citizens may object to new energy infrastructure in their localities which may cause delays in achieving the targets. To avoid such delays, it is crucial to understand what drives people's opinions. To explore people's opinions of different electricity generation and transmission technologies in Ireland, we conducted a nationally-representative survey. Concerning the drivers, we explicitly distinguish between socio-demographics, socio-psychological/political beliefs, and contextual/local factors. Our results show that people generally have positive views of RES technologies. While this indicates that Irish citizens agree with the move towards cleaner electricity sources, we find a reluctance amongst people to have these technologies located close to their homes. As for the drivers, we find that the respondents' socio-psychological and political beliefs are generally more important than most socio-demographics in driving their opinions and their tendency to oppose infrastructure development locally. This finding underlines the relevance for policy makers to understand which objectives people consider most important and how these judgements are related to their opinions of different energy technologies.
Keywords: 330; Local opposition; Renewable energy; Grid expansion; Energy policy objectives; Social acceptance